An ultralight, tiny, flexible six-axis force/torque sensor enables dexterous fingertip manipulations - Qian Mao; Zijian Liao; Shiqiang Liu; Jinfeng Yuan; Rong Zhu (Nature Communications)
Abstract Multi-dimensional mechanoreceptors are crucial for both humans and robots, providing omnidirectional force/torque senses to ensure dexterous and precise manipulations. Current six-axis force/torque sensors are bulky, heavy, and rigid with complicated sensing structures and high-cost manufacture. Although flexible force sensors have emerged recently, their perceptive dimension and performance are limited and still unsatisfactory for practical applications. Here, we propose an ultralight (0.30 g), tiny (fingertip size), and flexible six-axis force/torque sensor with a simple structure and low-cost fabrication. The sensor accurately perceives six-dimensional force/torque via capturing the spatial strain field of an elastic piezo-thermic material utilizing web-like scattered thin-film thermoreceptors. Integrating the sensor on the fingertip of humans or robots, we or robots can dexterously manipulate objects (e.g., open bottle cap), play games, and accomplish human-robot collaborative operations via easy fingertip-touch, demonstrating a broad prospect in applications of helping disabled and elderly people, intelligent robots, and virtual reality.